Investable poverty: Social investment states and the geographies of poverty management. (June 2020) - Baker, Tom; Evans, Joshua; Hennigan, Brian
The management of poverty is undergoing significant changes with the rise of social investment states. In this context, we examine how governmental concern about the long-term public cost of poverty is increasingly modulating the selection, sequencing and targeting of interventions that seek to manage poverty. Using examples drawn from the management of homelessness in Anglo-American cities, we outline a research agenda related to the objectification, economisation, and subjectification of 'investable poverty'. These emergent developments at the intersection of social investment and poverty management invite geographers and others to rethink where, when and how poverty management occurs.